Penyuluhan Peningkatan Kualitas Pelayanan Prima Pada Toko Baju Tulip Bengkulu - Yuliana, Alisa; Yulianti, Oni; Wijaya, Ermy; Sudarsono, Aji; Putri, Lydia Gustina (Jurnal Dehasen Untuk Negeri, 2024)
The title of this service is Counseling on Improving the Quality of Excellent Service at Tulip Clothing Stores Bengkulu. This service mainly wants to socialize and explain matters concerning Counseling on Improving the Quality of Excellent Service in determining the purchase of a product. as for the purpose of this service is so that the community can find out about improving Excellent Service at Tulip Clothing Stores. The results of the service show that the improvement of the Tulip Clothing Store's Prima Service is quite good and the prices are friendly, ranging from the cheapest to the most expensive ones there are also, for the completeness of the products in the Tulip Clothing Store is arguably quite complete ranging from children's clothing to adults, and there are also many choices of clothes, such as Muslim clothes, dresses, children's koko, robes and many more choices of clothes that suit your needs. So it is likely to attract customers to shop and buy products at the Tulip Clothing Store.